Postoperative pain and opioid use after breast reduction with or without preoperative nerve block. Issue 5 (May 2022) - LaFontaine, Samantha N.; Yao, Amy; Hwang, Lyahn K.; Draper, Lawrence; Benacquista, Teresa; Garfein, Evan S.; Weichman, Katie E.
Summary: Background: Physician-prescribed opioids have been implicated as key contributing factors in the current opioid epidemic in the United States. Breast reduction mammoplasty is one of the most commonly performed procedures in plastic surgery and patients are often prescribed large amounts of postoperative opioids. Here we investigate the effects of erector spinae nerve blocks on postoperative pain, opioid consumption, and quality of life after breast reduction. Methods: Following the institutional review board (IRB) approval, a prospective cohort study of some patients undergoing breast reduction mammoplasty at Montefiore Medical Center between June and September 2019 was undertaken. The patients were stratified into two cohorts for further analysis: those who received preoperative erector spinae nerve block and those who did not. Primary outcomes measures analyzed included Likert pain scores, patient-reported outcome measures, and opioid consumption for the first five postoperative days. Results: Forty-seven patients were enrolled in the analysis. Thirteen patients (28%) received nerve blocks, 34 (72%) did not. On average, the patients were prescribed 114.3 (±34.6) morphine equivalents postoperatively and they consumed 45% (±35.3) by the end of the first five days post-surgery. There were no significant differences between cohorts in morphine equivalents prescribed or consumed, postoperative pain scores, or patient-reported outcome measures. Conclusions: Following breast reduction mammoplasty, patients on average consumed < 50% of prescribed opioids, suggesting over-prescription of postoperative opioids for breast reduction recovery. Preoperative nerve block did not improve pain scores or decrease opioid consumption for the first five days after surgery.